APPLICATION OF THE MIND MAPPING TECHNIQUE TO IMPROVE STUDENT MEMORY IN PAI SUBJECTS - Ervina; Mardiana; Nurlidia Putri; Sri Rahayu Ratna Ningsih (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the effectiveness of the mind mapping method in improving student memory in Islamic Religious Education (PAI) subjects. Conventional learning methods are often less effective in stimulating students' memory because they only activate the left brain. Mind mapping, as a visual and holistic approach, is believed to overcome this limitation by involving the right brain in information processing. The results showed a significant improvement in students' memory and understanding of PAI materials after the implementation of the mind mapping method. Mind mapping's ability to systematically connect ideas and build comprehensive understanding contributed to the improvement in memory. This method proved to be flexible and effective for various PAI materials, including fiqh, SKI, akidahakhlak, and Al-Qur'an Hadith. This study recommends the use of mind mapping as an innovative learning strategy to improve the quality of PAI learning and student learning outcomes